Aristoteles Tentang Karakter: Aristotle On Character - Silalahi, Ubat Pahala Charles (Jurnal Filsafat Indonesia, 2025)
Character is important in investigating human nature, morality, and the pursuit of a fulfilling life. Character is a reality that is often interchangeable with the individual, so understanding character is used to understand a person. The modern world has developed Aristotle’s thoughts on character into separate research fields, so revisiting Aristotle’s original ideas can reduce the dichotomy. This research examines Aristotle’s various views on the nature and importance of human character. It reviews the various strands of Aristotle’s thought scattered throughout his writings to explain his distinctive perspective on character as a coherent and interconnected whole. This study uses a reflective systematic method to synthesize Aristotle’s views on character from the ethical, dramatic, and eudaimonic dimensions. The results of this research state that the core of Aristotle’s virtue ethics perspective is that developing virtues over time will maintain enduring character traits. The virtues are applied consistently through practical reasoning while maintaining a balanced approach between emotion and action. This development process involves individual choices and considerations. The Aristotelian framework of character is a continuous and dynamic process. This approach is a counterpoint to the deterministic and situational-based approach to human action. Aristotle identifies the development of moral and intellectual qualities as essential to achieving eudaimonia. Eudaimonia is the highest realization of human potential through reason. This concept embodies rationality as its foundation, thus strengthening the relationship. A virtuous character enables individuals to achieve self-sufficiency (αὐτάρκεια: autarkeia). Self-sufficiency is an important factor for achieving eudaimonia (εὐδαιμονία) as it reduces human dependence on external conditions for their well-being.